KHAT HABIT AND ITS HEALTH EFFECT. A NATURAL AMPHETAMINE - Dhaifalah, Ishraq; Santavy, Jiri (Biomedical papers, 2004)
Chewing the leaves of the khat shrub is common in certain countries of East Africa and Arabian Peninsula mainly Yemen. It has been established that a khat plant leaves contain an active psycho-stimulant substance known as cathinone that is similar in structure and pharmacological activity to amphetamine in affecting the CNS. Intoxication with khat is self-limiting but chronic consumption can cause certain health disturbances in the user and also lead to social and economic damage to the individual and the community. In recent years, several cases of intoxication have been observed outside the area of its use. In this view, the khat habit, its health effects and socioeconomic aspects are described with the political issue they imply.
Keywords: Khat/Natural amphetamine/History/Legality/Habit/Health eff ect